The Road to Success or Failure? Trends in Marijuana Use in Germany Immediately before and after Legalisation - Horváth-Bacsó, Bernadett (Magyar Rendészet, 2026)
Introduction: In the spring of 2024, Germany partially legalised marijuana use, allowing adults to possess and consume limited amounts of cannabis. This move sparked significant social and political debate, but also created new research opportunities for analysing the effects of drug policy. Aims: This study aims to analyse how marijuana consumption has changed in the months before and after legalisation. Is this path leading to success or failure? Methodology: The study was conducted using the most recent information and literature reviews available from 2023 onwards. The author reviewed content from various scientific fields to update and expand her knowledge of the subject. Result: Based on the data available so far, consumption has increased, especially among young adults (aged 18–29), but it is also evident that younger and younger people are trying cannabis. The increase in recent years is cause for concern. Currently, German consumers face the problem of difficulty in obtaining the legally permissible amount, mainly due to underdeveloped infrastructure and bureaucracy. According to surveys, most people tried the drug out of curiosity or for recreational purposes, while regular users mainly use it to relieve stress or treat sleep disorders. Some studies suggest that, in parallel with partial legalisation, the black market share of cannabis has also started to grow, as the delay in obtaining legal cannabis may result in people turning to illegal sources while waiting to purchase the legalised substance. Illegal dealers are also adapting to the changed situation by selling their products more cheaply and in larger quantities, making it easier for consumers to obtain the drug, even though more and more people would prefer controlled-quality, legally available products. It is also important to mention that the prescription of cannabis for medical purposes has increased many times over, which may hinder the proper functioning of the healthcare system and increase the risks of consumption, especially since it can now be prescribed electronically. The authorities are paying particular attention to protecting young people and strengthening prevention campaigns, but they believe that prevention alone is not enough. Conclusion: Overall, it can be said that the trend in marijuana consumption in Germany has not yet achieved the planned goal following partial legalisation, which, let us face it, is almost impossible in just one year. The German people do not want a complete ban again, and the regulation has caused conflicts between political parties, but further detailed research is needed to accurately assess the longer-term social, health and economic impacts.